Late gadolinium enhancement location and transcatheter ablation efficacy in a large cohort of patients affected by myocarditis with arrhythmic manifestation. (25th November 2020) - Persampieri, S; Bergonti, M; Gasperetti, A; Narducci, M.L; Perna, F; Catto, V; Carbucicchio, C; Di Biase, L; Basso, C; Andreini, D; Natale, A; Dello Russo, A; et al.
Abstract: Introduction: Myocarditis is a complex inflammatory disease, usually secondary to viral infections or immune system dysregulation, with extremely heterogeneous clinical manifestations. Among them, potentially life-threatening ventricular arrhythmias (VA) may present at any stage of the disease as an expression of myocardial electrical instability. Purpose: Our aim was to evaluate the efficacy of radiofrequency catheter ablation (RFCA) of VA in our large cohort of myocarditis, trying to understand the predictors of RFCA success. Methods and results: 144 patients (61 men; age 43 [29–54] years) with history of myocarditis with arrhythmic presentation (118 biopsy-proven, 82%) composed our population. At presentation, 26% of patients suffered of ventricular tachycardia (VT) while in 17% cardiac arrest occurred: overall 49 patients (35%) were implanted with an ICD. The median left ventricular ejection fraction (LVEF) was 58% (48–61%). An intensive non-invasive and invasive work-up was performed: 104 patients underwent cardiac magnetic resonance (CMR) that showed late gadolinium enhancement (LGE) in 67 of them (63%). In 37 patients LGE was found in the anteroseptal portion of the left ventricle: this pattern showed association with major arrhythmic relapse (VT and ventricular fibrillation) during follow up (Fig. 1; OR 4.0, CI 95% 1.14–14.1, p=0.03). 95 patients underwent endocardial RFCA, using contact electroanatomic mapping. Interestingly, in patients with anteroseptal LGE RCFA didn't affect significantly the arrhythmic relapse (OR 5, CI 95% 0.9–33, p=0.06). Otherwise RFCA prevent arrhythmic relapse in patients that showed LGE in ventricular portion other than the anteroseptal one (OR 0.027, IC 95% 0.002–0.40, p<0.01). During a median follow-up of 735 days (418–2168) 6 deaths occurred: logistic regression on all-cause death showed LVEF and VT at presentation as the only independent predictors for mortality (p=0.01). Conclusions: In myocarditis patients with VA, LGE pattern predicts arrhythmic relapse during follow-up. RFCA success rate is strictly linked to scar location, being significantly higher in patients with non-anteroseptal LGE. Funding Acknowledgement: Type of funding source: None